2016
DOI: 10.1007/s10815-016-0724-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of next-generation sequencing in preimplantation genetic diagnosis cycles for Robertsonian and reciprocal translocations

Abstract: Purpose The purpose of this study was to apply nextgeneration sequencing (NGS) technology to identify chromosomally normal embryos for transfer in preimplantation genetic diagnosis (PGD) cycles for translocations. Methods A total of 21 translocation couples with a history of infertility and repeated miscarriage presented at our PGD clinic for 24-chromosome embryo testing using copy number variation sequencing (CNV-Seq).Results Testing of 98 embryo samples identified 68 aneuploid (69.4 %) and 30 (30.6 %) euploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…Title and abstract screening resulted in 73 papers. Full text screening resulted in 26 publications fulfilling the inclusion criteria . No randomized controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Title and abstract screening resulted in 73 papers. Full text screening resulted in 26 publications fulfilling the inclusion criteria . No randomized controlled trials were identified.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 26 publications, six studies reported on the prevalence of mosaicism. One publication reported mosaicism on a per chromosome level only . The remaining five publications reported on mosaicism ranging from 0% (0/175 and 0/18 embryos) to 10.8% (11/102 embryos), with the two largest studies reporting 3.7 (42/1122 embryos) and 6.8% (44/646) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Next‐generation sequencing is a rapidly developed technology and has a great potential on the areas of PGD/preimplantation genetic screening. Recent studies utilizing this technique show promising results in the application on IVF …”
Section: Discussionmentioning
confidence: 99%
“…Recent studies utilizing this technique show promising results in the application on IVF. [24][25][26][27]…”
Section: Discussionmentioning
confidence: 99%